"To know or not to know…?" Push and pull in ever smokers lung screening uptake decision‐making intentions. (5th October 2018) - Tonge, Janet E.; Atack, Melanie; Crosbie, Phil A.; Barber, Phil V.; Booton, Richard; Colligan, Denis
Abstract: Background: In the United States, lung cancer screening aims to detect cancer early in nonsymptomatic current and former smokers. A lung screening pilot service in an area of high lung cancer incidence in the United Kingdom has been designed based on United States trial evidence. However, our understanding of acceptability and reasons for lung screening uptake or decline in a United Kingdom nontrial context are currently limited. Objective: To explore with ever smokers the acceptability of targeted lung screening and uptake decision‐making intentions. Design: Qualitative study using semistructured focus groups and inductive thematic analysis to explore acceptability and uptake decision‐making intentions with people of similar characteristics to lung screening eligible individuals. Setting and participants: Thirty‐three participants (22 ex‐smokers; 11 smokers) men and women, smokers and ex‐smokers, aged 50‐80 were recruited purposively from community and health settings in Manchester, England. Results: Lung screening was widely acceptable to participants. It was seen as offering reassurance about lung health or opportunity for early detection and treatment. Participant's desire to know about their lung health via screening was impacted by perceived benefits; emotions such as worry about a diagnosis and screening tests; practicalities such as accessibility; and smoking‐related issues including perceptions of individual risk and smoking stigma. Discussion: Decision making was multifaceted with indications that current smokers faced higher participation barriers than ex‐smokers. Reducing participation barriers through careful service design and provision of decision support information will be important in lung screening programmes to support informed consent and equitable uptake.